Hepatitis a: changes in the epidemiological pattern - Marinho, Rui Tato (2000)
Introduction: There is evidence, that is corroborated by several other authors, pointing toward a change in the epidemiological patterns of hepatitis A in various European, American, and even Asian countries. Knowing the current prevalence of anti-hepatitis A virus (anti-HAV) antibodies is thus imperative, all the more so that the anti-hepatitis A vaccine has begun to be marketed in Portugal. Objective: To assess the current prevalence of anti-HAV antibodies in an urban population of health professionals and medical students from the Santa Maria Hospital in Lisbon. Population: 526 subjects were studied, of which 325 were health professionals from diverse age and professional groups from the Santa Maria Hospital, and 201 were students from various pre-graduate years of the Medical School. Methods: Total anti-HAV antibodies were determined by an immune-enzymatic assay using a commercial kit. Results: The global prevalence of anti-HAV antibodies was 86.4% in health professionals, and 35.3% in students, this difference being statistically significant (p